Culturally Relevant Education: Think Local Within a Holistic Orientation. (2nd January 2021) - Pang, Valerie Ooka; Alvarado, Jose Luis; Preciado, Jose R.; Schleicher, Al R.
Abstract : Students bring valuable cultural ways of knowing and worldviews to the classroom. Teachers who build on student cultures are able to motivate and make learning more meaningful. We believe that teachers should Think Local within a holistic orientation to create a student-centered and culture-centered education that arises out of student cultural knowledge, life experiences, and belief systems. Like the Farm to Table movement in agriculture, teachers need to think about reaching students using a Think Local perspective. We highlight three examples of culturally relevant programs and how their holistic programs are based on thinking local. From these three cases, we recommend that teachers consider utilizing five cultural competencies that will assist them in integrating the local expertise of students into schooling.